Modelling Energy Consumption and Energy-Saving in High-Quality Olive Oil Decanter Centrifuge: Numerical Study and Experimental Validation - Antonia Tamborrino (Energies, 2019)
In this study, an energy consumption model of a decanter centrifuge was proposed, in particular for a technologically evolved machine equipped with an electromechanical recovery system. This model should be suitably coupled with an auto-adaptive controlling technique used to accurately manage the olive oil process. To achieve this goal, a solid physical and theoretical basis that simple to implement is required. To date there have only been limited scientific studies modelling energy consumption applied to the machines used in olive oil extraction processes. Therefore, the model was developed using fluid dynamic analysis and physical constraints to give it a solid basis. It was then simplified sufficiently for future implementation in automatic machine systems. The empirical model was validated through power measurements conducted in two harvesting seasons under varying operating conditions. The model estimates the power absorbed by the bowl and that produced and recovered by the screw, with high accuracy in each harvesting season. When considering the two harvesting seasons as a single season, the prediction accuracy remains considerable, despite a marginal increase in errors (correlation coefficient greater than 0.90). Finally, the model indicates that the screw conveyor speed is the most important parameter to achieve the desired energy recovery level, while the differential speed, which is a process parameter, has only a negligible impact on energy saving.